TRANSFORMASI DIGITAL MELALUI E-KATALOG LOKAL SEBAGAI BENTUK PEMBERDAYAAN USAHA MIKRO KECIL DAN MENENGAH DI BIRO PENGADAAN BARANG ATAU JASA DAN PEREKONOMIAN SEKRETARIAT DAERAH PROVINSI BALI - Rahayu, Ni Wika Putri; Prabawati, Ni Putu Anik; Purnamaningsih, Putu Eka (CITIZEN CHARTER, 2023)
Digital transformation is a change in activities from conventional to digital by utilizing the development of information technology. Local e-catalogs are a form of digital transformation carried out by the government in helping MSME players market their products digitally. The existence of this local Ecatalog is a form of empowerment carried out by the government in utilizing digital technology to help increase the growth and development of MSMEs. Bali Province is a province that has great MSME potential. The magnitude of the potential that it has has made the Provincial Government of Bali form a regional E-Catalog where the implementers are the Bureau of Procurement of Goods/Services and the Regional Secretariat of the Province of Bali. This research was conducted with the aim of finding out to what extent Digital Transformation Through Local E-Catalogs Is a Form of Empowerment of Micro, Small and Medium Enterprises in the Bureau of Procurement of Goods or Services and the Economy of the Provincial Secretariat of Bali. This study uses a qualitative descriptive research method using the Lucija, Vuksic', and Spremic' Digital Transformation Dimensions of 2019. The results obtained in this study are Digital Transformation Through Local E-Catalogs as a Form of Empowering Micro, Small and Medium Enterprises at the Bureau of Procurement of Goods or Services and the Economy of the Regional Secretariat of the Province of Bali is quite good on several indicators such as strategy, human resources, and innovation in the implementation of the Local E-Catalog. However, there are still several indicators that have not been optimal in the implementation of the Local E-Catalog, such as organization and technology.